Low prevalence of CWH43 variants among Finnish and Norwegian idiopathic normal pressure hydrocephalus patients: a cohort-based observational study - Räsänen, Joel; Helisalmi, Seppo; Heikkinen, Sami; Raivo, Joose; Korhonen, Ville E.; Martiskainen, Henna; Junkkari, Antti; Grenier-Boley, Benjamin; Bellenguez, Celine; Oinas, Minna; Avellan, Cecilia; Frantzen, Janek; et al. (BMC, 2025)
Background Heterozygous CWH43 loss-of-function (LOF) variants have been identified as iNPH risk factors, with 10-15% of iNPH patients carrying these variants in cohorts from the US. Mouse model harboring CWH43 LOF variants display a hydrocephalic phenotype with ventricular cilia alterations. Our aim was to study the effect of CWH43 variants on disease risk and clinical phenotype in Finnish and Norwegian iNPH cohorts.
Methods We analyzed CWH43 LOF frameshift deletions (4:49032652 CA/C, Leu533Ter and 4:49061875 CA/C, Lys696AsnfsTer23) in Finnish iNPH patients from the Kuopio NPH registry (n = 630) and FinnGen (iNPH n = 1 131, controls n = 495 400), and Norwegian iNPH patients from EADB (n = 306). The Kuopio and Norwegian cohorts included possible and probable iNPH patients based on the American-European iNPH guidelines. FinnGen cohort included iNPH patients based on ICD-10 G91.2 with the exclusion of secondary etiologies, and controls having no diagnosis of hydrocephalus.
Results In the Kuopio cohort of Finnish iNPH patients, 2.9% carried CWH43 variants (Leu533Ter 2.1%, Lys696AsnfsTer23 0.8%), with one homozygous Leu533Ter carrier. In FinnGen, 3.1% of iNPH patients carried heterozygous variants (Leu533Ter 2.6%, Lys696AsnfsTer23 0.5%) compared to 2.5% of controls (p = 0.219, OR = 1.23, 95% CI 0.85-1.72), with no effect on disease risk or onset age. Importantly in the FinnGen cohort, none of the 23 compound heterozygote or 59 homozygote individuals had hydrocephalus diagnosis. In the Norwegian iNPH cohort, 5.2% of patients were heterozygous variant carriers (Leu533Ter 3.3%, Lys696AsnfsTer23 2.0%). No differences in clinical phenotype (age, triad symptoms, shunt response, vascular comorbidities) were found between carriers and noncarriers in any cohort. However, 74% of variant-carrying iNPH patients in FinnGen were female, compared to 47% of noncarriers (p = 0.002). Pedigrees indicated no autosomal dominant co-inheritance of iNPH and the CWH43 variants.
Conclusions We studied the iNPH-associated CWH43 LOF variants for the first time on a population-scale. Contrary to previously reported findings in smaller cohorts, our study revealed a low prevalence of these variants in the population-scale Finnish iNPH cohort, with no effect on disease risk of iNPH. The prevalence in the Norwegian iNPH cohort was also low compared to previous studies.